Self-reported psychotic-like experiences: differences by age and associated psychopathology - Becerra-García, Juan Antonio; Sanchez-Gutierrez, Teresa; Barbeito, Sara; Calvo, Ana (Behavioral Psychology-psicologia conductual, 2023)
This study aims to explore the differences in psychopathological symptoms that may exist in the general adult population with or without psychotic-like experiences (PLEs), depending on the age range. The presence of PLEs, self-reported general psychopathological symptomatology, and different sociodemographic and psychosocial characteristics were assessed in 216 participants without any record of personal psychiatric antecedents. The sample was divided into young adults (18-35 years) and mature adults (36-60 years). The young adults showed a higher expression of PLEs (33.6%). The mature adults with PLEs presented more psychopathological symptoms in the dimensions of hostility-anger, somatization, depression, and anxiety than mature adults without PLEs. Young adults with PLEs showed significantly more symptoms in the same dimensions, and in the obsession-compulsion dimensions, paranoid ideation, and psychoticism, than participants of this age without PLEs. PLEs are more frequent in people between 18-35 years old; however, PLEs can be present in different age ranges and could serve as an alert to high levels of affective and anger-hostility symptoms.
Keywords: psychotic experiences; general population; adults; age groups; psychopathology; JCR; Scopus